Deterioration due to delayed icing and its impacts on the nutritional quality of Malabar travally (Carangoides malabaricus). (7th November 2012) - Jeyasanta, K. I.; Prakash, Sinduja; Carol, G. R.; Patterson, Jamila
Summary: Effect of delayed icing of the fish Carangoides malabaricus was assessed using chemical and microbial methods to determine the impacts on the nutritional quality and sensory changes. The shelf life of the fishes iced immediately after harvest had a shelf life of 18 days, whereas the delay of icing for 4, 6, 8 and 10 h shortened the shelf life to 14, 10, 6 and 3 days respectively. The spoilage indicators, such as trimethylamine nitrogen, Total volatile basic nitrogen, free fatty acids, peroxide value, thiobarbituric acid and pH values, significantly increased ( P  < 0.05) during the storage period of fishes with delayed icing. The total bacterial count also increased during the storage period and due to quality deterioration, the protein and lipid contents were found significantly low ( P  < 0.05). This study showed that chemical and microbial changes of the sample are well correlated with nutritional and sensory qualities so that immediate icing is important for maintaining the quality and shelf life of C. malabaricus .